2023
DOI: 10.1002/aenm.202302837
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Binding Energy in Organic Polymers: Experimental Considerations and Tuning Prospects

Somayeh Kashani,
Jeromy James Rech,
Tuo Liu
et al.

Abstract: Discrepancies in reported values of exciton binding energy (Eb) for organic semiconductors (OSs) necessitate a comprehensive study. Traditionally, Eb is defined as the difference between the transport gap (Et) and the optical gap (Eopt). Here, the Eb values of PBnDT‐TAZ polymer variants are determined using two commonly employed methods: a combination of ultraviolet photoemission spectroscopy and low‐energy inverse photoemission spectroscopy (UPS‐LEIPS) and solid‐state cyclic voltammetry (CV). Eb values obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 121 publications
(178 reference statements)
0
1
0
Order By: Relevance
“…Relatively little research has been done on vacancy-ordered perovskites for solar cells. Studies have shown that Cs 2 TiX 6 (X = Br and I) possesses multiple desirable attributes including good stability and high optical absorption coefficients in the visible light ranges. More recently, Zhao et al and Reyes-Francis et al, respectively, pointed out the ease of synthesis and high power conversion efficiency (PCE) of Cs 2 TiX 6 . , The impact of large exciton binding energy in Cs 2 TiX 6 may potentially be mitigated through atomic substitution or by changing the dielectric environment of the insulating organic layer. The aforementioned discussions suggest that Cs 2 TiX 6 holds the potential for use in solar cells. However, existing calculations and experiments have proven that both Cs 2 TiBr 6 and Cs 2 TiI 6 have some shortcomings that limit their further applications. , First, these two materials have quasi-direct bandgaps with indirect bandgaps between Γ (valence band maximum, VBM) and X (conduction band minimum, CBM), which are detrimental to their photovoltaic performance .…”
Section: Introductionmentioning
confidence: 99%
“…Relatively little research has been done on vacancy-ordered perovskites for solar cells. Studies have shown that Cs 2 TiX 6 (X = Br and I) possesses multiple desirable attributes including good stability and high optical absorption coefficients in the visible light ranges. More recently, Zhao et al and Reyes-Francis et al, respectively, pointed out the ease of synthesis and high power conversion efficiency (PCE) of Cs 2 TiX 6 . , The impact of large exciton binding energy in Cs 2 TiX 6 may potentially be mitigated through atomic substitution or by changing the dielectric environment of the insulating organic layer. The aforementioned discussions suggest that Cs 2 TiX 6 holds the potential for use in solar cells. However, existing calculations and experiments have proven that both Cs 2 TiBr 6 and Cs 2 TiI 6 have some shortcomings that limit their further applications. , First, these two materials have quasi-direct bandgaps with indirect bandgaps between Γ (valence band maximum, VBM) and X (conduction band minimum, CBM), which are detrimental to their photovoltaic performance .…”
Section: Introductionmentioning
confidence: 99%